Financial development and economic growth: panel evidence from BRICS - Guru, Biplab Kumar; Yadav, Inder Sekhar (Universidad ESAN. ESAN Ediciones, 2019)
Purpose - The purpose of this paper is to examine the relationship between financial development and economic growth for five major emerging economies: Brazil, Russia, India, China and South (BRICS) during 1993 to 2014 using banking sector and stock market development indicators. Design/methodology/approach - To begin with, the study first examined some of the principal indicators of financial development and macroeconomic variables of the selected economies. Next, using generalized method of moment system estimation (SYS-GMM), the relationship between financial development and growth is investigated. The banking sector development indicators used in the study include size of the financial intermediaries, credit to deposit ratio (CDR) and domestic credit to private sector (CPS), whereas the stock market development indicators are value of shares traded and turnover ratio. Also, some macroeconomic control variables such as inflation, exports and the enrolment in secondary education were used. Findings - The examination of the principal indicators of financial development and macroeconomic variables have shown considerable differences between the selected economies. Results from the dynamic one-step SYS-GMM estimates confirm that in presence of turnover ratio, all the selected banking development indicators such as size of financial intermediaries, CDR and CPS are positively significantly determining economic growth. Similarly, in presence of all the selected banking sector development indicators, value of shares traded is found to be positively significantly associated with economic growth. However, the same is not true when turnover ratio is regressed in presence of banking sector variables. Overall, the evidence suggests that banking sector development and stock market development indicators are complementary to each other in stimulating economic growth. Practical implications - A positive association between financial development and growth indicates that the policymakers should take necessary measures toward simultaneous development of both banking sector as well as stock market for inducing growth. Originality/value - The present paper attempts to examine the relationship between financial development and growth using both banking sector and stock market development indicators which has not been attempted before for BRICS. Also, most of the existing studies are found in case of developed economies. This paper tries to fill this void by studying five major emerging economies.

Objetivo - El propósito de este documento es examinar la relación entre el desarrollo financiero y el crecimiento económico de cinco importantes economías emergentes: Brasil, Rusia, India, China y el Sur (BRICS) durante 1993 a 2014 utilizando indicadores de desarrollo del sector bancario y del mercado de valores. Diseño / metodología / enfoque - Para empezar, el estudio examinó en primer lugar algunos de los principales indicadores de desarrollo financiero y variables macroeconómicas de las economías seleccionadas. A continuación, utilizando el método generalizado de estimación del sistema de momentos (SYS-GMM), se investiga la relación entre el desarrollo financiero y el crecimiento. Los indicadores de desarrollo del sector bancario utilizados en el estudio incluyen el tamaño de los intermediarios financieros, el índice de crédito a depósitos (CDR) y el crédito interno al sector privado (CPS), mientras que los indicadores de desarrollo del mercado de valores son el valor de las acciones negociadas y el índice de rotación. Asimismo, se utilizaron algunas variables de control macroeconómico como la inflación, las exportaciones y la matrícula en la educación secundaria. Recomendaciones - El examen de los principales indicadores de desarrollo financiero y las variables macroeconómicas ha mostrado diferencias considerables entre las economías seleccionadas. Los resultados de las estimaciones dinámicas de SYS-GMM en un solo paso confirman que, en presencia del índice de rotación, todos los indicadores de desarrollo bancario seleccionados, como el tamaño de los intermediarios financieros, CDR y CPS, determinan de manera positiva y significativa el crecimiento económico. De manera similar, en presencia de todos los indicadores de desarrollo del sector bancario seleccionados, el valor de las acciones negociadas se asocia de manera positiva y significativa con el crecimiento económico. Sin embargo, no ocurre lo mismo cuando se hace una regresión del índice de rotación en presencia de variables del sector bancario. Implicaciones prácticas - Una asociación positiva entre el desarrollo financiero y el crecimiento indica que los formuladores de políticas deben tomar las medidas necesarias para el desarrollo simultáneo tanto del sector bancario como del mercado de valores para inducir el crecimiento. Originalidad / valor - El presente artículo intenta examinar la relación entre el desarrollo financiero y el crecimiento utilizando indicadores de desarrollo del sector bancario y del mercado de valores, lo que no se había intentado antes para los BRICS. Además, la mayoría de los estudios existentes se encuentran en el caso de economías desarrolladas. Este documento intenta llenar este vacío mediante el estudio de cinco grandes economías emergentes.
Keywords: Economic growth; Crecimiento económico; https://purl.org/pe-repo/ocde/ford#5.02.04